Campo deportivo integral acuático para la rehabilitación física San José del Guaviare (2021)
This research refers to the issue of physical rehabilitation through water, taking into account the initial problem that is the armed conflict, due to this many people have been left with physical and emotional consequences, an architectural project is carried out focused on the potentialization of physical rehabilitation through water sports, ensuring that the infrastructure allows the user to integrate and give a second chance in their quality of life, a new alternative for improvement for the inhabitants of the municipality, promoting the integration of spaces that allow therapy more effective for the user, linking the natural elements that are found around such as the Guaviare river and the jungle that surrounds it and thus creating comfort in the rehabilitation areas due to the fact that nature gives great support to the sensory motor, causing different emotions in the disabled. Within the project there are different kinds of pools such as the therapeutic one and the semi-Olympic pool that accompanies the rehabilitation, group or individual therapy spaces supported by gyms and it should not be noted that the circulation by means of a ribbon that ties all the spaces and thus articulating them in a way that does not obstruct the passage of the disabled.